Science and Religion in Dialogue - Figas-Skrzypulec, Justyna (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2011)
Sprawozdanie z kursu letniego Science and Religion in Dialogue, The Faraday Institute for Science and Religion, Uniwersytet Cambridge, 17-23 lipca 2011.